Coupled analytical-numerical approach for determining hydrodynamic responses of breakwater with multiple OWCs. (November 2021) - Han, M.M.; Wang, C.M.
Abstract: A coupled analytical-numerical approach has been developed that allows one to study the hydrodynamic responses of breakwaters of arbitrary geometry that have multiple OWCs with horizontal openings. The approach incorporates the eigenfunction of the OWC fluid domain into the boundary element method, which automatically satisfy the boundary condition at the OWC opening. As a result, the exact geometry of the OWCs no longer needs to be modelled and the number of elements will be largely reduced especially when dealing with 3D breakwaters. With the present approach, a class of 2D OWC-integrated breakwater concepts in existing literature was simulated for validation and parametric study. The approach was then applied to the 3D breakwater with multiple OWCs under slender OWC assumptions, and the numerical results obtained are compared to data from a reduced scale model test. The 2D case studies show that the present approach is able to generate accurate results on reflection and transmission, wave loads, and energy extraction efficiencies with a higher efficiency than conventional boundary element method. Comparison of 3D results with the model test results shows that the prediction of the natural frequency and the wave reflection and transmission coefficients are in good agreement. Highlights: A hybrid boundary element method has been developed for the analysis of breakwater of arbitrary geometry with multiple OWCs. A class of 2D OWC-integrated breakwater design concepts has been analysed with present approach. Comparison of numerical results with analytical and experimental data show good agreements.